PREFERENSI KONSUMEN TERHADAP MINYAK KELAPA MURNI (VIRGIN COCONUT OIL/VCO) DI KABUPATEN KONAWE (Consumers Preferences toward Virgin Coconut Oil in Konawe Regency) - Yudha Ramadhan Bahari; Bahari Bahari; R. Marsuki Iswandi (Jurnal Sosio Agribisnis, 2018)
The emergence of many healthy oil products in market has caused consumers to have different preference in choosing a product that suits their needs. Consumer’s decision in choosing a product is highly determined by attributes attached to the product. The purpose of this study was to analyze consumers’ attitude in buying VCO oil, to determine stages involved in a decision made by consumers when buying VCO oil, and analyze VCO oil attributes that are mostly considered by consumers. Methods of data analysis were chi square analysis, fishbein analysis, and descriptive analysis. Results of the study showed that the consumers’ attitude towards VCO oil was positive and they agreed with the product. The consumers also had positive preference to VCO oil. Stages involved in the consumers’ decision-making were identifying their needs by searching for the advantages, directly seeking for information to sellers, alternative buying decision that was influenced by peers and relatives, post purchase evaluation. The attributes of VCO oil that received most consideration from consumers were consecutively the followings: health benefits 77.50percent, distinctive aroma of coconut oil 75 percent, water clarity 73.75 percent, quality and packaging 72.50 percent, and price and availability 71.25 percent.Keywords: VCO; preference; attitude; product attributes